The Challenges of Student in Indonesia after College Graduates with Career Choice Start: Evidence from Ten Private Universities in Jakarta - Setiawan, William Vincent; Fattah, Andi Marlin; Puspitaningrum, Angga (Journal the Winners: Economics, Business, Management, and Information System Journal, 2019)
This research examined the problem of graduates’ and students’ who began entering the workforce in which they have creative potential during college and could be combined university studies with activities in the world of work. A qualitative approach was used in terms of testing how students get a job in the labor market. Data analysis method used semi-structured interviews to 50 graduates in 10 private universities in Jakarta. This research focused on gender aspects that challenge graduates. This research finds that student while working is more dominant among women than men, where many companies in Indonesia are more looking for female workers. The labor market must be balanced with the number of graduates in Indonesia so that human resources can be used to the fullest; there is no unemployment and improve poverty rates in the country. Most male and female graduates have worked after graduating and getting jobs according to their field of expertise. There are students who pursue their master’s programs to support their careers and as employees in Indonesian companies.